2019
DOI: 10.1097/dad.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Inhibitor–Associated Granulomatous Dermatitis: A Report of 3 Cases

Abstract: Cutaneous toxicities associated with BRAF inhibitor treatment in patients with metastatic melanoma have been well described. We present a rare association of granulomatous dermatitis in association with the BRAF inhibitor vemurafenib. Three patients with metastatic melanoma all presented with asymptomatic papular eruptions 8–21 months into vemurafenib therapy. Skin biopsies confirmed the diagnosis of granulomatous dermatitis. Other causes of granulomatous dermatitis including infectious agents and sarcoid were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…30 Skin SLR presents more commonly with papules and plaques, but can also appear as subcutaneous nodules on the arms or legs, both early and late after treatment initiation. 4,6,9,11 14,31,32 Finally, Korman et al 33 reported a case of granulomatous dermatitis within a benign blue nevus. Granulomatous infiltration of tattoos has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Skin SLR presents more commonly with papules and plaques, but can also appear as subcutaneous nodules on the arms or legs, both early and late after treatment initiation. 4,6,9,11 14,31,32 Finally, Korman et al 33 reported a case of granulomatous dermatitis within a benign blue nevus. Granulomatous infiltration of tattoos has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases have been reported as granulomatous involvement of specific organs, e.g., granulomatous myocarditis, 8 hepatitis, 9 nephritis, 10 uveitis, 11 and dermatitis. 12 16 Cases of systemic sarcoid-like granulomatosis have also been reported. 17 Finally, Dando et al 3 reviewed all the above reported cases using the term ‘drug- induced SLR’.…”
Section: Discussionmentioning
confidence: 99%
“…Bland emollients, topical keratolytics, and tretinoin cream have been used to treat KP. Like in adults, granulomatous dermatitis can occur many months after the onset of vemurafenib therapy 96 . Interestingly, there is only one reported case of squamous cell carcinoma arising in a child treated with a BRAF inhibitor 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Like in adults, granulomatous dermatitis can occur many months after the onset of vemurafenib therapy. 96 Interestingly, there is only one reported case of squamous cell carcinoma arising in a child treated with a BRAF inhibitor. 15 The rarity in childhood suggests that chronic actinic damage may play a role in the eruptive squamoproliferative lesions, which is seen in 20%-30% of adults, on BRAF inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Acneiform eruption [123,124] Alopecia (telogen effluvium) [136] Basal cell carcinoma [137] Cheilitis [9] Granulomatous eruption [138][139][140] Grover's disease [141] Hand-foot skin reaction [142] Milia [9] Panniculitis [143,144] Pruritus [10,14] Vitiligo [145,146] Xerosis [9] 5. MEK-Inhibitors…”
Section: Less Frequently Encountered Brafi-associated Cutaneous Adver...mentioning
confidence: 99%